2019
DOI: 10.1038/s41467-019-09865-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: RNA m6A methylation regulates the epithelial mesenchymal transition of cancer cells and translation of Snail

Abstract: N6 -Methyladenosine (m 6 A) modification has been implicated in the progression of several cancers. We reveal that during epithelial-mesenchymal transition (EMT), one important step for cancer cell metastasis, m 6 A modification of mRNAs increases in cancer cells. Deletion of methyltransferase-like 3 (METTL3) down-regulates m 6 A, impairs the migration, invasion and EMT of cancer cells both in vitro and in vivo. m 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
427
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 478 publications
(461 citation statements)
references
References 67 publications
18
427
0
Order By: Relevance
“…To test the utility of dCas13b-ALKBH5 for targeted m 6 A methylation, we selected potential candidate transcripts according to the following rules: 1) The RFKM of transcript is greater than 300 in m 6 A-seq according to our previous study; and 2) Only one m 6 A peak site was identified for one transcript. For those transcripts bearing m 6 A variated in cells undergoing EMT (in our previous study) 31 , they are preferentially selected due to the more dynamic variation of m 6 A. Finally, the transcript of CYB5A was chosen to investigate the effects of dCas13b mediated demethylation system (Figure 2 A and Figure S2A).…”
Section: The Dm 6 Acrispr Induced M 6 a Demethylation At Cds Increasementioning
confidence: 99%
“…To test the utility of dCas13b-ALKBH5 for targeted m 6 A methylation, we selected potential candidate transcripts according to the following rules: 1) The RFKM of transcript is greater than 300 in m 6 A-seq according to our previous study; and 2) Only one m 6 A peak site was identified for one transcript. For those transcripts bearing m 6 A variated in cells undergoing EMT (in our previous study) 31 , they are preferentially selected due to the more dynamic variation of m 6 A. Finally, the transcript of CYB5A was chosen to investigate the effects of dCas13b mediated demethylation system (Figure 2 A and Figure S2A).…”
Section: The Dm 6 Acrispr Induced M 6 a Demethylation At Cds Increasementioning
confidence: 99%
“…RNA extraction with Trizol (Invitrogen) and real time PCR were performed according to the protocol used in our previous study [21].…”
Section: Rna Extraction and Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…Considering that METTL3 is critical to mRNA m 6 A methylation, we questioned whether the m 6 A of TGFβ1 mRNA regulated its expression. Firstly, we assumed from the m 6 A sequencing results from our previous study (Accession code GSE112795) [21] that TGFB1 mRNA contained two m 6 A modification peaks in 5 UTR and exon 1, respectively (Figure 2a). We performed m 6 A RNA-immunoprecipitation (RIP) qPCR and confirmed that m 6 A levels of TGFB1 mRNA reduced significantly in Mettl3 Mut/− cells (Figure 2b).…”
Section: A Negatively Regulates the Mrna Stability Of Tgfb1mentioning
confidence: 99%
See 2 more Smart Citations